Effective Release of Intracellular Enzymes by Permeating the Cell Membrane with Hydrophobic Deep Eutectic Solvents. (26th November 2019) - Cao, Jun; Wu, Rong; Dong, Qihui; Zhao, Linguo; Cao, Fuliang; Su, Erzheng
Abstract: An efficient and green method is crucial for the recovery of intracellular biological products. The major drawbacks of the conventional cell disruption method are nonselectivity and enzyme denaturation. The permeability of hydrophobic deep eutectic solvents (DESs) to the cell membrane was studied, for the first time, and then hydrophobic DESs were innovatively applied to release intracellular enzymes from recombinant Escherichia coli . After optimization, a DES suspension of l ‐menthol/oleic acid (0.5 %, v / v ) showed the highest release yield of intracellular enzyme. Compared with that released by sonication, a release yield of phospholipase D (PLD) of up to 114.58 % was achieved, and the specific activity was increased by 1.96 times. The microstructure of the cell membrane under different treatments was observed by using an electron microscope to understand the permeation of DESs to the cell membrane. The feasibility and applicability of the proposed release method in industrial applications were also demonstrated. The effective and green release method of intracellular enzymes developed herein has bright prospects for industrial application to replace traditional cell disruption methods. A preliminary study on the permeability of hydrophobic DESs to the cell membrane showed that there would be a potential application prospect of hydrophobic DESs not only in releasing intracellular contents, but also in seeking new green penetrating agents. Abstract : Opening barriers : The permeability of hydrophobic deep eutectic solvents (DESs) through the cell membrane is studied and these DESs are applied to release intracellular enzymes from recombinant E. coli cells. This effective and green release method for intracellular enzymes has prospects for industrial application to replace traditional cell disruption methods.